Do Gender and Education Matter for Company Financial Performance? Evidence from Indonesian Companies - Adam Zakaria; Suherman Suherman; Agung Dharmawan Buchdadi; Sukma Andika Rahmayanti; Muhammad Edo Suryawan Siregar (Jurnal Manajemen dan Kewirausahaan, 2021)
This research is aimed to investigate the influence of gender diversity and educational level in board of commissioner on the performance of non-financial company listed in Indonesia Stock Exchange for 2013-2017 period. Gender diversity as the first research variable was measured by female existence as the head of commissioner, female existence on board of commissioner and its proportion. Meanwhile, education level of female in board of commissioner as the second variable was measured with dummy 1 for master and doctoral graduate and 0 for other levels. Next, the company performance variable is proxied with a return on assets (ROA), return on equity (ROE), and Tobin’s Q. The model employed in this research was an unbalanced data panel using fixed and random effect model approach. The results show that gender diversity has a significant impact on ROA, but an insignificant impact on ROE and Tobin’s Q. Further, education does not have a significant impact on financial performance. In general, board characteristics do not have an important role in determining financial performance.